FAKTOR-FAKTOR YANG MEMPENGARUHI PASANGAN USIA SUBUR (PUS) TERHADAP PEMILIHAN ALAT KONTRASEPSI IUD DI KELURAHAN PIJORKOLING KECAMATAN PADANGSIDIMPUAN TENGGARA KOTA PADANGSIDIMPUAN TAHUN 2019 - RAHMADHANI SYAFITRI (STIKes Mitra Husada Medan, 2021)
IUD contraception is a contraceptive device that is placed in the uterus which is relatively more effective when compared to the pill, injection, and condom method. Pijorkoling Health Center in 2019, it is known that the number of fertile age couples in the District of Padangsidimpuan Tenggara is 1,782 and there are 1,206 active family planning acceptors (67,6). That the selection of Non-Hormonal Contraception is much lower, where the percentage of IUD contraceptive users in the Pijorkoling Village is only 98 acceptors (3.3%). This study aims to determine the factors that influence fertile age couples (PUS) on the selection of IUD contraceptives in Pijorkoling Village, Southeast Padangsidimpuan Subdistrict, Padangsidimpuan City in 2019. This research is descriptive with a cross-sectional design. The population in this study were all KB acceptors residing in Kelurahan Pijorkoling, a sample of all KB acceptors residing in Kelurahan Pijorkoling totaling 98 acceptors. Statistical analysis was performed by univariate, bivariate, and multivariate analyzes.. From the results of PUS research using IUD contraception as much as 66.3%. The analysis shows that two variables that have a significant influence, namely socio-culture (p = 0.010), and husband's support (p=0.001) with the selection of IUD contraception and there is no significant association relationship between education (p=0.071), knowledge (p=0.812), the distance of family planning services (p=0.285), with the selection of IUD contraception. The results of multivariate analysis obtained that the dominant factor in the selection of IUD contraceptives was husband support with a logistic regression equation with a value (p=0.001) with an OR value of 1.961. Suggestions are expected for health workers and KB fieldworkers to play an active role in raising PUS awareness in the form of continuous public outreach to increase PUS participation in the use of IUD birth control. Keywords: Husband Support, Socio-Culture, PUS, IUD Contraception